Interdisciplinary, praxis-focused auto-ethnography: using autobiography and the values discussion to build capacity in teachers. - Barnes, Jonathan Mason (Advances in Social Sciences Research Journal, 2014)
This paper is about what makes for resilience within a challenging profession. A teacher who has remained idealistic and positive throughout 42 years in education examines the psychological and practical sources of his personal positivity. The complex and bespoke methodology invented to answer the question, ‘What sustains a fulfilling life in education’ is offered as an approach to ethnography aimed at personal development, applicable to both education researchers and practitioners. The method, Interdisciplinary, praxis focussed autoethnography, is not just as a novel means of examining motivations in an individual but is presented as offering a new perspective on staff development in teaching and perhaps other caring professions. The powerful effect of this research on the researcher’s practice is discussed in the context of its impact on the development of an approach to capacity building based upon values, creativity and friendship.